A Study On The Impact Of Information Systems On The Management and Operations of Private Education Institutions In Malaysia - Hussin, Norriza; Rajamanickam, Leelavathi (International Journal of Psychosocial Rehabilitation, 2020)
— This paper explores the use of technology on the management and operation of private education institutions in Malaysia. Private education in Malaysia ranges from all levels starting from nursery schools up to the tertiary education. This sector has been regarded as a balance to substantiate the public education of the overwhelming number of students. Issues in managing and operating education institutions have been appraised from time to time by each institution or school. The Private Education Division under the Ministry of Education of Malaysia has issued guidelines on the management and operation of the private education. The concern of this paper regulates around the study on the impact of information systems in facilitating the management and operation issues. This paper will describe the general literature on private education, followed by the selected issues under management and operation. Other sections in this paper will highlight the aspects of information systems and its impact of the management and operation matters. The aim of this paper is to identify the vital areas from the management and operation. These vital components are to be examined as a potential research area with further objectives on delivering an efficient services in the private education institutions or schools in Malaysia. Greater concerns will be highlighted as further recommendations in future research work to enhance the quality of education delivered in the of private education with the use of information systems.